2012
DOI: 10.3928/01913913-20110712-02
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Year Review of Pediatric Traumatic Open Globe Injuries in an Urban U.S. Population

Abstract: The visual prognosis in pediatric open globe injury is poor. The zone of injury may correlate with poor final visual acuity, risk of retinal detachment, and subsequent need for an enucleation. The final predicted visual acuity correlated well with the observed final visual acuity in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
56
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 20 publications
16
56
2
1
Order By: Relevance
“…Furthermore, children with an initial VA less than CF had significantly worse final VA than children with better initial VA. Wound localization did not significantly affect functional success, although scleral injuries (i.e., more posterior lacerations) were associated with poorer visual outcomes, as suggested by previous studies [6,15,16,21]. Injuries involving the posterior segment had a significantly worse final VA, as in the reports of Bunting et al and Tok et al [22,23].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Furthermore, children with an initial VA less than CF had significantly worse final VA than children with better initial VA. Wound localization did not significantly affect functional success, although scleral injuries (i.e., more posterior lacerations) were associated with poorer visual outcomes, as suggested by previous studies [6,15,16,21]. Injuries involving the posterior segment had a significantly worse final VA, as in the reports of Bunting et al and Tok et al [22,23].…”
Section: Discussionsupporting
confidence: 61%
“…CGI constitute a large proportion of mechanical globe injuries in childhood, but visual and anatomical outcomes seem to be poorer in OGI than CGI [5][6][7][8][9]. There have been limited and conflicting studies on the prognosis of OGI and factors affecting the prognosis [4][5][6][10][11][12][13][14][15][16]. Therefore, there is still a need for detailed reports to increase our understanding of this potentially sightthreatening injury.…”
Section: Introductionmentioning
confidence: 99%
“…Lesniak et al 31 report no significant differences between the final visual acuities and the visual acuities predicted by OTS in children. Sharma et al 32 propose that the OTS calculated at the initial examination may be of prognostic value in children with penetrating eye injuries.…”
Section: Discussionmentioning
confidence: 94%
“…This is why globe injuries are particularly penetrating at 75% but only 10% for rupture in our study. Other authors have come up with different rates such as 54% and 65.7% for penetrating trauma 34% and 22.4% for rupture of the globe [11] [12]. But Gilbert et al [13] in their study have rather found that globe ruptures were more frequent with a varying frequency from 39% to 43.2%.…”
Section: Years As the Campus Teaching Hospital Of Lomé Is The Only Omentioning
confidence: 95%